Temporal uncoupling between demographic and genetic metrics in fisheries assessment: the European hake case study - Fernández-Míguez, María; Pita, Alfonso; Gómez, Antonio; Presa, Pablo (Frontiers in Marine Science, 2023)
An authentic ecological transition for fisheries sustainability requires the integration of all relevant biological criteria in assessment models. Current analyses aim to dissect the evolution of some demographic and genetic metrics in the overharvested Southern European hake fishery in the last four decades. Demographic data were drawn from official records of ICES while genetic data were obtained from a lustrumbased sampling series between 1975 and 2014. Opposite to NAPS-microsatellites (Non-Adaptive Polymorphic Systems), APS-microsatellites (Adaptive Polymorphic Systems) succeeded at detecting genetic erosion at the maximum population overharvest in lustrum 1996 -2000, a phenomenon also confirmed with the molecular variation of the mtDNA cytochrome b gene. We show that the maximum demographic mortality Z_NSSB (1986 -1990) predated both, the maximum genetic effective mortality Z_LDNe (1991 -1995) as well as the maximum cohort-based mortality 𝑍𝑍 ̅ _ICES (1996 -2000). Such temporal uncoupling between demographic and genetic metrics suggests that official cohort analyses are far from assessing the real biological status of the Southern European hake fishery as to achieve its sustainability-oriented advice.